2001
DOI: 10.1080/gye.15.4.251.258
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-induced secretion of growth hormone ,insulin-like growth factor I and prolactin by human breast cancer explants

Abstract: The aim of the study was to evaluate the potential of human breast cancer tissue to secrete growth hormone (GH), insulin-like growth factor I (IGF-I) and prolactin in response to 10(-7) M progesterone stimulation. Explants were divided according to estrogen receptor (ER)/progesterone receptor (PR) phenotype (ER(-)PR(-); ER(+)PR(-); ER(+)PR(+); ER(-)PR(+)). Our results show distinct differences in cultured breast cancer tissue responses to progesterone stimulation with regard to secretion of proliferative agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…For example, estradiol exerts its neuroprotective effects on the brain in synergy with IGF-I [156]. Reciprocal interactions between PROG, GH and IGF-I have also been reported in different experimental systems [157][158][159]. Thus, it is likely that the hormone and growth factor environment will influence the effectiveness of a steroidal treatment and vice versa.…”
Section: Discussionmentioning
confidence: 89%
“…For example, estradiol exerts its neuroprotective effects on the brain in synergy with IGF-I [156]. Reciprocal interactions between PROG, GH and IGF-I have also been reported in different experimental systems [157][158][159]. Thus, it is likely that the hormone and growth factor environment will influence the effectiveness of a steroidal treatment and vice versa.…”
Section: Discussionmentioning
confidence: 89%
“…The expression of GH in the mammary gland is thought to be largely dependent upon progesterone [127,128], and mammary GH production is suppressed by ovariectomy [129] and by progesterone receptor antagonists [125,130]. It is thus of note that the progesterone receptor is colocalized with GH in the mammary gland [130].…”
Section: Mammary Tissuementioning
confidence: 94%
“…They suggested that progestagens might be mitogenic in the breast tissue. We previously reported the stimulatory effect of progesterone on the activation of local hGH/IGF-I/IGF binding protein axis in breast tissue expressing progesterone receptors [5,6]. Moreover, we showed that the differences in secretion of hGH and IGF-I from breast tissue explants depended on the type of progestagens used and the steroid receptor phenotype of both malignant and adjacent non-malignant tissue [7].…”
Section: Introductionmentioning
confidence: 63%
“…Primary tumor explants were prepared according to Gregoraszczuk et al [5]. Briefly, explants from the malignant tissue and surrounding non-malignant tissue were trimmed into 0.5 cm 3 pieces, weighed and incubated in 2 ml of M199 phenol red free medium (Sigma, M3769) containing 5% of calf serum.…”
Section: In Vitro Incubation Of Mammary Glandmentioning
confidence: 99%